The demand and recycling potential for lithium, cobalt, and nickel in the European electric-mobility transition - Chen Tang; Arnold Tukker; José M Mogollón (Environmental Research Communications)
To address the increasing greenhouse gas emissions in the EU transport sector, the EU has announced climate plans to promote zero-emission passenger vehicles, in practice likely to be implemented in the form of electric vehicles (EVs) due to their technology maturity. This study applies a dynamic material flow model to evaluate the future demand for lithium, cobalt, and nickel in the EU transport sector based on these climate plans and to assess the potential for their secondary supply through 2040. Our results suggest that growing demand for EVs will lead to at least a 21-fold increase in annual demand and a 105-fold stock expansion of these metals in 2040, compared to the 2021 EV sales levels. The available secondary supply of these metals will increase from the early 2030 s based on the updated EU Battery Directive, reaching 20%-30% of the cumulative material demand by 2040. An accelerated adoption of EVs increases the potential and the need for earlier secondary raw material recovery, underscoring the necessity to promptly develop sufficient recycling facilities in the EU. Shifting towards less critical metal-containing EV batteries, reducing the EV battery capacity, and extending the lifetime of the EV batteries will facilitate the reduction of primary demand.